PENGARUH SISTEM PENGENDALIAN INTERN, BUDAYA ORGANISASIONAL, DAN SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN - Iwan Satriawan; Ahmad Rifa'i; Muaidy Yasin (Master of Accounting Universitas Trunojoyo Madura, 2016)
This study aims to examine the effect of the internal control system, organizational culture, and human resources to the quality of financial reporting. The research variables consist of independent variables, the internal control system (X1), organizational culture (X2), and human resources (X3), and the dependent variable is the quality of financial reporting. The study population were employees of financial operators on the Sumbawa Regency SKPD scope. Samples were taken using probability sampling technique, which is proportional stratifiet random sampling, which is composed of the Finance Administration, Head of Sub Division of Finance, and Treasurer Expenditure.Distribution of the questionnaire were 63 copies, and all of them can be used and analyzed. Processing and analysis of data using multiple linear regression method. Partial assay results indicate that the system of internal control, and human resources have a significant effect on the quality of financial reporting. While the organizational culture not significant effect on the quality of financial reporting. Simultaneous test results show the system of internal control, organizational culture, and human resources have a significant effect on the quality of financial reporting. In the measurement of the independent variables the model goodness of internal control systems, organizational culture, and human resources can explain the dependent variable quality of financial reports by 46% and the balance of 54% is explained by other variables not included in the regression models were constructed.